2021
DOI: 10.1002/jcsm.12744
|View full text |Cite
|
Sign up to set email alerts
|

Targeting interleukin‐1 for reversing fat browning and muscle wasting in infantile nephropathic cystinosis

Abstract: Background Ctns À/À mice, a mouse model of infantile nephropathic cystinosis, exhibit hypermetabolism with adipose tissue browning and profound muscle wasting. Inflammatory cytokines such as interleukin (IL)-1 trigger inflammatory cascades and may be an important cause for cachexia. We employed genetic and pharmacological approaches to investigate the effects of IL-1 blockade in Ctns À/À mice. Methods We generated Ctns À/À Il1β À/À mice, and we treated Ctns À/À and wild-type control mice with IL-1 receptor ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Increased levels of systemic inflammatory cytokines, such as interleukin (IL)-1, IL-6, and TNF-α, are well-documented in patients with CKD [ 94 , 123 , 124 ]. Higher baseline IL-1β levels are associated with a more rapid decline in phase angle, an indicator for muscle function, after one-year HD [ 125 ].…”
Section: Therapeutic Strategies For Muscle Wastingmentioning
confidence: 99%
“…Increased levels of systemic inflammatory cytokines, such as interleukin (IL)-1, IL-6, and TNF-α, are well-documented in patients with CKD [ 94 , 123 , 124 ]. Higher baseline IL-1β levels are associated with a more rapid decline in phase angle, an indicator for muscle function, after one-year HD [ 125 ].…”
Section: Therapeutic Strategies For Muscle Wastingmentioning
confidence: 99%
“…Further supporting a role for inflammasome activation in the pathogenesis of cystinosis in Ctns −/− mice, there was a significant increase in the renal expression of inflammasome-related genes, and an increase in the circulating levels of IL-18 was also observed [ 35 ]. Recently, the increased mRNA and protein levels of IL-1β were also found in the affected skeletal muscles of Ctns −/− mice [ 41 ]. However, to date, it remains to be studied in which cells, in vivo, in the cystinotic kidney and other affected organs, the inflammasome is activated.…”
Section: Inflammasome Activation In Cystinosismentioning
confidence: 99%
“…Prencipe et al targeted the activated NLRP3 inflammasome pathway in cystinosis through the cathepsin B inhibitors CA-074Me and diphenyleneiodonium chloride, which decreased the secretion of IL-1β induced by the cystine crystals in the peripheral blood monocytes and suppressing the inflammatory cascade that should follow, thereby paving the way for another mechanism that can be targeted in cystinosis patients [ 18 ]. Cheung et al studied Ctns −/− mice for both the genetic deletion of Il1b as well as treatment with the recombinant IL-1 receptor antagonist (IL-1ra) anakinra, which led to an attenuation of the cachexia phenotype in cystinotic mice, supporting the efficacy of the IL-1 anti-inflammatory-targeted therapy on adipose browning and muscle wasting in nephropathic cystinosis [ 41 ]. Adding to this effect, Gonzalez et al demonstrated significant beneficial actions of the leptin receptor blockade, which is a well-known immunomodulatory cytokine and hormone on the cachexia phenotype in Ctns −/− mice.…”
Section: Targeting Inflammation As a Potential Therapeutic Option In Cystinosismentioning
confidence: 99%
“…It should be born in mind, that patients with INC displayed elevated levels of Il1β, Il18, and caspase 1 compared to healthy controls, but they also displayed significantly elevated levels of Il18 compared to patients with Familial Mediterranean Fever, a prototypical autoinflammatory disease [ 54 ]. Recently, Cheung et al, demonstrated that by treating Ctns −/− mice with the Il1 receptor antagonist Anakinra they were able to attenuate the cachexia phenotype and correct the abnormal expression of the main biomarkers of beige adipose cells and adipocyte tissue browning, and to attenuate 12 of the 20 main, differentially expressed genes in Ctns −/− mice [ 55 ]. Anakinra treatment also normalized muscle weight and fiber size and decreased infiltration in muscle fat [ 55 ].…”
Section: Towards An Interplay Between Bone Adipocytes and Musclesmentioning
confidence: 99%
“…Recently, Cheung et al, demonstrated that by treating Ctns −/− mice with the Il1 receptor antagonist Anakinra they were able to attenuate the cachexia phenotype and correct the abnormal expression of the main biomarkers of beige adipose cells and adipocyte tissue browning, and to attenuate 12 of the 20 main, differentially expressed genes in Ctns −/− mice [ 55 ]. Anakinra treatment also normalized muscle weight and fiber size and decreased infiltration in muscle fat [ 55 ]. These results were close to those observed earlier by the same team using vitamin D [ 51 ], questioning again the role of vitamin D in inflammation regulation.…”
Section: Towards An Interplay Between Bone Adipocytes and Musclesmentioning
confidence: 99%